Ocular surface squamous neoplasia in HIV-positive and HIV-negative patients and response to 5-fluorouracil in Angola - Nutt RJ (Dove Medical Press, 2014)
Robert J Nutt,1 John L Clements,2 William H Dean3 1Faculty of Medicine and Dentistry, University of Bristol, Bristol, UK; 2Boa Vista Eye Clinic, Benguela, Angola; 3Bristol Eye Hospital, Bristol, UK Background: Ocular surface squamous neoplasia (OSSN) is becoming increasingly prevalent and aggressive in Sub-Saharan Africa. It is a phenomenon linked with human immunodeficiency virus (HIV) infection, although association rates in Angola are currently unknown. A topical treatment that is effective in HIV-positive and HIV-negative individuals may be preferable to surgery in some contexts. We aimed to estimate the proportion of OSSN associated with HIV in Angola and to report on the success of topical 5-fluorouracil as a primary treatment in HIV-positive and HIV-negative patients.Methods: Photographs of OSSNs taken at presentation and following treatment with 5-fluorouracil in patients presenting to Boa Vista Eye Clinic, Angola, between October 2011 and July 2013 were grouped into HIV-positive and HIV-negative groups and analyzed to compare presenting features and treatment response. Eighty-one OSSNs were analyzed for clinical features and 24 met the inclusion criteria for analysis of treatment response.Results: Eighty-two patients presented with OSSN between October 2011 and July 2013. Twenty-one (26%) were HIV-positive and typically had OSSNs that exhibited more pathological features than those in HIV-negative patients. Twenty-four (29%) patients met the inclusion criteria for analysis of treatment response; of these, 26 (91%) OSSNs in both groups displayed at least partial resolution after one treatment course. In the HIV-positive group, five of eight patients displayed complete resolution, two showed partial resolution, and one failed. In the HIV-negative group, five of 16 showed complete resolution, ten of 16 had partial resolution, and one failed.Conclusion: Individuals presenting with OSSN in Angola are more likely to have HIV infection compared with the general population. Regardless of HIV status, 5-fluorouracil drops can be an effective strategy for management of OSSN without incurring the costs and risks of surgery in the developing world setting. Keywords: ocular surface squamous neoplasia, 5-fluorouracil, Angola, Sub-Saharan Africa